KOMPONEN PENUNJANG KURIKULUM PENDIDIKAN AGAMA ISLAM (IBTIKAR: Jurnal Studi Islam dan Sosial, 2024)
Past education should be a reflection of future education. The good is from the past and the bad is left behind. This is done to find solutions to face globalization and developments in a time that is very different from the past. The philosophy of education and Islamic educational thought in this case must also provide a response to all these changes and developments. Using qualitative descriptive research. The basic concept of ideal Islamic education by paying attention to relevant teaching materials used in the learning process is one that can adapt to current developments without forgetting the values ​​of the Islamic religion in the world of education, as well as considering the principles and supporting components in preparing Islamic education. Islamic religious education curriculum. so that educational goals can be achieved in accordance with what is expected in educational development.